ANALISIS KANDUNGAN CADMIUM (Cd), TIMBAL (Pb) DAN FORMALDEHID PADA BEBERAPA IKAN SEGAR DI KUB (KELOMPOK USAHA BERSAMA) BELAWAN, KECAMATAN MEDAN BELAWAN TAHUN 2015 - putri sihol; evi naria; wirsal hasan (Lingkungan dan Kesehatan Kerja, 2015)
ABSTRACT Fresh fish is the type of fish which has the same characteristic as living fish, in shape, smell, taste and texture, hasn’t gone through preserving process or any other further processing. The fish which is taken mostly comes from Belawan Sea, with the size of 1 kg, 0.5 kg an 0.3 kg. One of the closest fish market with the Belawan Sea is KUB (Kelompok Usaha Bersama). The purpose of this research is to find out the content of cadmium (Cd), metal (Pb) and formaldehyde in the fresh fish which comes from KUB Belawan. The method is descriptive survey to analize the content of cadmium (Cd), lead (Pb) and formaldehyde in some fresh fish. The result showed that the level of cadmium (Cd) in tuna fish (Euthynnus affinis) with the size of 1 kg, 0,5 kg and 0,3 kg are 0,04 mg/kg, 0,01 mg/kg and 0,003 mg/kg and in white snapper fish (Lates calcarifer) are 0,01 mg/kg, < 0,003 mg/kg and < 0,003 mg/kg. The result showed that the level of lead (Pb) in tuna fish with the size of 1 kg, 0,5 kg and 0,3 kg are 0,167 mg/kg, 0,131 mg/kg and 0,101 mg/kg and in white snapper fish are 0,140 mg/kg, < 0,0025 mg/kg and < 0,0025 mg/kg. Formaldehyde showed is negative result. Based on SNI 7387:2009 regarding the maximum limit of heavy metal pollution in food product, which was drafted by taking into account the Ditjen POM Decision No.03725/B/SK/VII/1989, the level of cadmium and lead in tuna fish and white snapper are under the treshold limit value which are 0,1 mg/kg and 0,3 mg/kg. The highest level of cadmium and lead was found in fish with the bigger size and the value of formaldehyde in fishes that were taken from KUB Belawan is negative. The fish from Belawan Sea is safe to consume, but it’s better to consume the small size fish instead of the bigger ones.